2017
DOI: 10.3390/nu9040338
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Insufficiency Exacerbates Adipose Tissue Macrophage Infiltration and Decreases AMPK/SIRT1 Activity in Obese Rats

Abstract: Obesity is recognized as a state of chronic low-grade systemic inflammation due to adipose tissue macrophage infiltration and production of proinflammatory adipokines. Decreased vitamin D status is associated with obesity. The specific aim of the present study is to investigate the effects of vitamin D on obesity-induced adipose tissue inflammation. Male Sprague-Dawley rats were randomized and fed a normal diet (NOR, 1000 IU vitamin D/kg diet), a 45% high-fat diet (HF, 1000 IU vitamin D/kg diet), or a 45% high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 64 publications
2
82
0
Order By: Relevance
“…In addition, as AMPK enhances sirtuin 1 by increasing NAD/NADH ratio and decreases AT macrophage infiltration and inflammation, both have been proposed as key regulators to prevent obesity and obesity-related metabolic dysfunction. A recent study conducted by Chang et al [59] described that vitD deficiency significantly decreased mRNA levels of oxidation-related genes. Moreover, significant decrements of sirtuin 1 and AMPK activity were noted in obese rats fed with a vitD-insufficient diet.…”
Section: Vitd and Inflammationmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, as AMPK enhances sirtuin 1 by increasing NAD/NADH ratio and decreases AT macrophage infiltration and inflammation, both have been proposed as key regulators to prevent obesity and obesity-related metabolic dysfunction. A recent study conducted by Chang et al [59] described that vitD deficiency significantly decreased mRNA levels of oxidation-related genes. Moreover, significant decrements of sirtuin 1 and AMPK activity were noted in obese rats fed with a vitD-insufficient diet.…”
Section: Vitd and Inflammationmentioning
confidence: 98%
“…Consequently, the immune cells play an important role in AT and immune homeostasis. A decreased vitD status is associated with obesity, and recent in vitro studies have described that 1,25(OH) 2 D exerts anti-inflammatory action on adipocytes [48,59]. VitD promotes a lower chemokine and cytokine release by adipocytes and the chemotaxis of monocytes.…”
Section: Vitd and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…1,25(OH) 2 D 3 supplementation has been shown to reduce a unique circulating monocyte cholesterol pool in type 2 diabetes patients, the deficiency of which significantly promoted cholesterol accumulation and polarized macrophages toward the M2 phenotype in LPS‐stimulated THP1‐macrophages by decreasing plasma HDL levels and by decreasing the expression of LXR and ABCA1 . Moreover, decreased VD status reduced FAO‐related genes such as CPT1α, PGC1α, PPARα, and UCP1, and eventually exacerbated ATM infiltration and inflammation in obese rats . These studies suggest that VD is an important link between lipid metabolism and the immune‐inflammatory system.…”
Section: Micro‐environmental and Intracellular Metabolism On Atm Polamentioning
confidence: 88%
“…Vitamin D (VD), a fat‐soluble vitamin, is well known for its roles in calcium and bone metabolism. Even though it cannot provide energy like sugar and fat, VD plays active roles in metabolism in vivo . Epidemiological studies have shown that VD insufficiency or deficiency is common in obesity‐related metabolic diseases, which has harmful effects on obesity‐induced AT inflammation, including increased AT expansion, immune cell infiltration, and inflammatory status in rodent models .…”
Section: Micro‐environmental and Intracellular Metabolism On Atm Polamentioning
confidence: 99%